2014
DOI: 10.1111/trf.12694
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus DNA viral load determination in hepatitis B surface antigen–negative Swiss blood donors

Abstract: The highly sensitive HBV NAT assay with a threshold significantly below 10 IU/mL is a valuable alternative to anti-HBc and a less sensitive HBV NAT screening in blood donor screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…It remains controversial whether the number of intercepted infectious HBsAg‐negative donations outweighs the loss of anti‐HBc–positive noninfectious donors. While Germany, Canada, and the Netherlands have recently implemented anti‐HBc screening, Australia and Switzerland decided against it, and implemented ID‐NAT screening to limit potential donor loss . To our knowledge this is the first national evaluation of anti‐HBc donor screening in a setting with existing HBV NAT MP6 screening (plus HBsAg testing), in a population not previously tested for anti‐HBc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains controversial whether the number of intercepted infectious HBsAg‐negative donations outweighs the loss of anti‐HBc–positive noninfectious donors. While Germany, Canada, and the Netherlands have recently implemented anti‐HBc screening, Australia and Switzerland decided against it, and implemented ID‐NAT screening to limit potential donor loss . To our knowledge this is the first national evaluation of anti‐HBc donor screening in a setting with existing HBV NAT MP6 screening (plus HBsAg testing), in a population not previously tested for anti‐HBc.…”
Section: Discussionmentioning
confidence: 99%
“…The (estimated) prevalence of OBI in donor populations of low‐endemic countries strongly depends on the LOD of HBV NAT screening and varies between 0.1% and 3.7% . Recent studies from Switzerland and South Africa using ID‐NAT emphasize that the majority of donors with OBI (75 and 61%, respectively) have viral loads below 20 IU/mL and would slip through HBV NAT MP6 screening . Since virtually all donors with OBI have detectable anti‐HBc, the residual risk associated with OBI below the limit of HBV NAT detection will be eliminated by universal anti‐HBc screening .…”
Section: Discussionmentioning
confidence: 99%
“…Another concern refers to the detection limit that should be considered in donor screening programs. In a recent study [69], it was shown that a hypothetical detection limit below 5 IU/ml could be advisable since in a cohort of Swiss donors 1.2% of the reactive samples had a viral load below 10 IU/ml.…”
Section: Detection Of Occult Hepatitis B Infections In Blood Donorsmentioning
confidence: 99%
“…Occult HBV infection (OBI) was defined by an international workshop held in 2008 as the "presence of HBV DNA in liver (with a viral load of < 200 IU/mL or undetectable HBV DNA in the serum) of individuals testing hepatitis B surface antigen negative by currently available assays" (6)(7)(8). The prevalence of OBI carriers was shown to be more prominent since the introduction of HBV DNA nucleic acid testing (NAT) in blood transfusion centers across all continents with yield varying from 0.1% to 4.16% (2)(3)(4)(5)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%